2023
DOI: 10.3390/ijms24021139
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatilla vulgaris Inhibits Cancer Proliferation in Signaling Pathways of 12 Reporter Genes

Abstract: This study aimed to examine if methanolic extracts of Pulsatilla vulgaris Mill. can inhibit HeLa cell proliferation through the modulation of cancer-related signaling pathways. The cytotoxicity and chemical composition of P. vulgaris leaves and root extracts were also determined. Research showed that root extract of P. vulgaris inhibited 12 signaling pathways in a cervical cancer cell line and the most potent activation inhibition was observed for MYC, Notch, Wnt, E2F, Ets, Stat3, Smad, Hdghog, AP-1, and NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
1
3
0
Order By: Relevance
“…Oleanolic and ursolic acids, i.e., the most commonly occurring triterpenoids, were found previously in flowers and inflorescences of C. laevigata [36], S. nigra [37] and V. minor [38]; however, the detailed analysis of other accompanying triterpenoids and phytosterols was performed in the present study for the first time. In turn, the obtained results revealed that P. vulgaris flowers contained only trace amounts of these acids in a free form, which was in accordance with the recent finding that this plant appeared to be rich in triterpenoid saponins [39], i.e., triterpenoid glycosides that were not determined in the present study. On the other hand, on the basis of the previous report on the occurrence of triterpenoids in R. rugosa accessory fruit [40], the occurrence of significant amounts of these compounds in a free form in the flowers of this plant could be predicted.…”
Section: Discussionsupporting
confidence: 93%
“…Oleanolic and ursolic acids, i.e., the most commonly occurring triterpenoids, were found previously in flowers and inflorescences of C. laevigata [36], S. nigra [37] and V. minor [38]; however, the detailed analysis of other accompanying triterpenoids and phytosterols was performed in the present study for the first time. In turn, the obtained results revealed that P. vulgaris flowers contained only trace amounts of these acids in a free form, which was in accordance with the recent finding that this plant appeared to be rich in triterpenoid saponins [39], i.e., triterpenoid glycosides that were not determined in the present study. On the other hand, on the basis of the previous report on the occurrence of triterpenoids in R. rugosa accessory fruit [40], the occurrence of significant amounts of these compounds in a free form in the flowers of this plant could be predicted.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies reported that Pulsatilla compounds play a crucial role in inhibiting the growth of tumor cells, particularly in liver, lung and breast cancer ( 56 , 57 ). B4G6, a derivative of 23-HBA, has been demonstrated to induce mitochondrial apoptosis by triggering ROS accumulation and the opening of calcium-dependent permeability transition pores, thereby inhibiting the proliferation of HepG2, Hep3B, Bel-7402 and HepG2/ADM cell lines ( 58 ). B4G2 exhibits a potent inhibitory effect on HepG2 cell proliferation and induces mitochondrial autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to discover novel anticancer therapeutics, more than 900 pure natural compounds isolated at the National Center for Natural Product Research of the University of Mississippi repository were screened through a battery of cancer-related signaling pathway assays to identify compounds exhibiting unique patterns of anticancer activities [8,9]. Among the compounds screened, we identified a new, unique activity/mechanism for gnetin H (GH), a resveratrol trimer, and an electrophilic compound that has been previously described by different research groups to inhibit the growth of several cancer cell lines [10][11][12][13][14][15].…”
Section: Of 22mentioning
confidence: 99%